Financial Literacy Analysis in Encouraging Sustainable MSMEs Business Performance Mediation Financial Access and Adoption Fintech - Priyo Prasetyo; Priyo Priyantoro (Green Publisher Indonesia, 2025)
Many MSMEs still face fundamental challenges such as limited access to formal financing, low financial literacy, and slow adoption of digital technology, including fintech. Sustainable business performance requires business actors not only to survive economically but also to manage their businesses efficiently, have a long-term orientation, and adapt to market and technological dynamics. The purpose of this study is to analyze the role of financial literacy on the sustainable performance of MSMEs by examining the mediating role of financial access and fintech adoption. The method in this study uses the Structural Equation Modeling – Partial Least Squares (SEM-PLS) approach with the assistance of SmartPLS software. This research is a quantitative explanatory study, with the population consisting of MSMEs in Kediri City. The results show that financial literacy does not directly affect MSME performance, but it plays an important role in expanding financial access. This financial access then becomes a significant mediating pathway that connects financial literacy with business performance. Thus, financial literacy will only contribute effectively to MSME performance if it is accompanied by the ability to access and utilize financial services productively. Meanwhile, fintech adoption has been shown to play no significant role, either directly on performance or as a mediator between financial literacy and business performance. This indicates that the use of financial technology remains limited to basic transaction functions and has not been fully integrated into MSME business strategies.